Dynamic of Plantation of Oil Palm Smallholdings in Riau Province Sumatra Indonesia - Duryat Duryat; Sylvain Raflegau; Marck Phillip Cannon (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
Smallholder's plantations represent 44% of oil palm in Indonesia, and they were known to have agronomic performance much lower than Estate ones. So there is large room for increasing the yield with sustainable cropping system. To better understand the heterogeneity of smallholder's plantations, an agricultural diagnosis has been implemented in a specific place, Riau Province of Sumatra. This study led to well characterize the dynamics of plantation in the region and the diversity of rationalities. Among eight existing types of smallholding plots, there were only three types with yield hardly lower than those of the estate plantations. This reinforced the interest to implement diagnosis through the nutritional status of palms using data from foliar diagnosis and soil analysis. Keywords: dynamic of plantation, palm oil, smallholders, Sumatra